Truth and reconciliation in Serbia - Nikolić-Ristanović Vesna Ž. (Temida, 2004)
The paper provides a general review of the current situation concerning the truth and reconciliation in Serbia. The existing attitude toward the past in Serbia is examined through an analysis of relations toward it and through the analyses of bottom up and top-down initiatives. In this respect, the paper’s focus is on the following: the media, nongovernmental organizations the individual citizen, state organs, primarily the authorities and criminal justice system, and the international community. The citizens’ opinions that were brought out in the panel discussions organized by the Victim logy Society of Serbia, within the project From remembering the past towards a positive future, and that refer to the need for a process of truth and reconciliation and the obstacles and difficulties related to that, are pointed out as well. Particular attention is devoted to the obstacles and difficulties related to the absence of a clear position of the authorities to the counter-productive decisions of the international community and the still negative role of the media that fail to deal broadly with the issues of truth and reconciliation.